In vivo structural dynamic analysis of the dragonfly wing: the effect of stigma as its modulator. (10th June 2019) - Kumar, Amit; Kumar, Navin; Das, Rakesh; Lakhani, Piyush; Bhushan, Bharat
Abstract : The flapping of the dragonfly forewing under in vivo condition has been analysed by image correlation technique to get an insight of its structural dynamics. The modal parameters such as flapping frequency, natural frequencies, mode shapes and modal strain have been obtained that will facilitate the biomimetic design of wings for micro air vehicles. The stigma, which is a pigmented spot at the leading edge of the wing near the tip having heavier mass, takes an active role in the real-time flapping by shaping its trajectory as eight-shaped, which enhances the drag coefficient and stroke efficiency. The extra mass on it and its removal transformed the trajectory into two different elliptical and oval shapes, respectively, which reduced the drag coefficient and stroke efficiency of the flapping wing by altering the flapping kinematics. This article is part of the theme issue 'Bioinspired materials and surfaces for green science and technology (part 2)'.